Job satisfaction and organizational commitment of nurses in teaching hospitals affiliated to Kerman University of Medical Sciences - Habibolah Rezaei; Bahareh Bahmanbijari; Amin Beigzadeh; Seyed Mostafa Seyed Askari; Elham Khadir (مجله ایرانی آموزش در علوم پزشکی, 2017)
Introduction: Job satisfaction and organizational commitment are two important factors in predicting organizational behavior. The purpose of this study was to assess the extent of organizational commitment and job satisfaction of nurses in teaching hospitals of Kerman University of Medical Sciences. Methods: In this descriptive cross-sectional study, statistical population included 1058 nurses working in teaching hospitals of Kerman University of Medical Sciences in 2014 of whom 281 nurses were selected through proportionate stratified random sampling. Data collection tools were Luthans’ job satisfaction and Allen & Meyer’s organizational commitment questionnaires. Validity and reliability of these questionnaires had been previously confirmed in Iran. Data were analyzed using descriptive statistics and nonparametric Spearman correlation coefficient statistical tests. Results: A total of 250 questionnaires were completed by the participants of whom 200 (80%) were female and 50 (20%) were male. 59.6% of the nurses were highly satisfied with their job and 62.3% had an average organization commitment. There was a significant relationship between job satisfaction and organizational commitment (P-Value<0.05) (r=0.2). Conclusion: Considering the significant relationship between job satisfaction and organization commitment, a comprehensive national research should be carried out to evaluate job satisfaction of nurses and identify the problems in order to take effective steps toward enhancement of quality of services.